2006
DOI: 10.1002/ejoc.200600230
|View full text |Cite
|
Sign up to set email alerts
|

New Metal‐Catalyzed Synthesis of Quinoline and Chromene Skeletons

Abstract: Alkoxy‐functionalized butadienylboronic esters have been synthesized starting from α,β‐unsaturated acetals and cross‐coupled with both N‐protected and N‐unprotected 2‐bromo‐ and 2‐iodoaniline, and with 2‐iodophenol. In particular, N‐tosyl‐protected dienylanilines can be transformed under mild conditions into quinolines and quinolinones, in the presence of a PdII catalyst. Moreover, the cross‐coupling reaction between butadienylboronic esters and iodophenol directly affords chromenes that can be successively tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…An alternative, however, is to allow aromatization via b-X elimination, which does not undergo reductive elimination, and allows the palladium to remain in the Pd(II) state upon aromatization. An example of this is in the recent work of Venturello, where it was observed that the palladium-catalyzed intramolecular addition of N-tosyl aniline derivatives to dienes allows the generation of quinolines (Scheme 6.33) [43]. This latter reaction is believed to proceed in a similar fashion to that above, wherein coordination of the palladium catalyst to the diene initiates nucleophilic attack.…”
Section: Heteroatom Additions To Alkenesmentioning
confidence: 81%
“…An alternative, however, is to allow aromatization via b-X elimination, which does not undergo reductive elimination, and allows the palladium to remain in the Pd(II) state upon aromatization. An example of this is in the recent work of Venturello, where it was observed that the palladium-catalyzed intramolecular addition of N-tosyl aniline derivatives to dienes allows the generation of quinolines (Scheme 6.33) [43]. This latter reaction is believed to proceed in a similar fashion to that above, wherein coordination of the palladium catalyst to the diene initiates nucleophilic attack.…”
Section: Heteroatom Additions To Alkenesmentioning
confidence: 81%